English Language Teachers’ Professional Journey and Construction of their Identity - Neupane, Bharat Prasad (Journal of Interdisciplinary Studies in Education, 2023)
This study presents the trajectories of identity construction of three English language teachers from Nepal analyzing their storied life from school teachers to university professors employing three-dimensional professional development model forwarded by Padwad and Dixit (2014) to explore effective mediation by state agencies, culture and the policies, appropriate support from the organizations, and the bottom-up initiatives by the teachers in their professional development. Besides, professional journey derived from in-depth interview of the participants is analyzed employing Wenger's (1999) communities of practice, particularly engagement, alignment, and imagination, as theoretical categories to discover their professional identities. The analysis revealed that passion for language, creativity, and motivation to learn English language during childhood encouraged them to study English initially. In addition, inspiration from their teachers during their schooling and later a competitive working environment motivated them experiment with innovative approaches to teaching and establishing themselves in the profession. Furthermore, diversification in university teaching according to university requirements and resultant divergence from the professional root ultimately transformed their identity beyond English teachers. Finally, university policy, customization of teachers as per the university requirement, and their survival strategy as English teachers in a university where technical subjects are given priority have impacted their professional identities.